2005
DOI: 10.1177/0021934704270254
|View full text |Cite
|
Sign up to set email alerts
|

Responding to Prisoner Reentry, Recidivism, and Incarceration of Inmates of Color

Abstract: This article introduces a systemic model for rehabilitation that uses the expungement procedure, a preexisting statute, as a tool to reduce incarceration and recidivism and help probationers succeed in their reentry into mainstream society as taxpaying citizens and concomitantly alleviate the burden on taxpayers for maintaining prisoners. It culminates with a call to the African American and Hispanic communities to partner with the penal system and lawmakers to find solutions to the devastating effects of incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…Criminologists have consistently found that African Americans have higher recidivism rates than whites and Hispanics. This is for several reasons, including a higher likelihood that police will catch African Americans committing crimes and the disproportionate number of African Americans living in impoverished neighborhoods (Marbly & Ferguson, 2005;Travis, 2005). Race is a dichotomous variable in this analysis, with African Americans as the reference group.…”
Section: Methodsmentioning
confidence: 99%
“…Criminologists have consistently found that African Americans have higher recidivism rates than whites and Hispanics. This is for several reasons, including a higher likelihood that police will catch African Americans committing crimes and the disproportionate number of African Americans living in impoverished neighborhoods (Marbly & Ferguson, 2005;Travis, 2005). Race is a dichotomous variable in this analysis, with African Americans as the reference group.…”
Section: Methodsmentioning
confidence: 99%
“…Marbley and Ferguson (2005) provide a more definitive map in their call for communities of color to address inmates of color. "There is an urgent need to have a systematic way of partnering with businesses, colleges and universities, faith-based institutions, and communities in an effort to reinstate reformed prisoners back into society as contributing, taxpaying citizens" (Marbley & Ferguson, 2005, p. 637).…”
Section: Leipold's Community Critiquementioning
confidence: 99%
“…Promoting healthy parenting behaviors by father may prevent future problems (Marshall, English, & Stewart, 2001). A number of contextual factors can affect paternal involvement and outcomes sought by CPS, including relationship status between the mother and father of the child, history of incarceration, poverty and SES, and other neighborhood factors (Connell, Bergeron, Katz, Saunders, & Tebes, 2007; Marbley & Feruguson, 2005). Despite these concerns, the relationship between fathering and child protection has been overlooked in the literature (Brown, Callahan, Strega, Walmsley, & Dominelli, 2009).…”
Section: Introductionmentioning
confidence: 99%